Printable Two-Dimensional V2O5/MXene Heterostructure Cathode for Lithium-Ion Battery. Issue 2 (2nd February 2021) - Wang, Yang; Lubbers, Ties; Xia, Rui; Zhang, Yi-Zhou; Mehrali, Mohammad; Huijben, Mark; ten Elshof, Johan E.
Abstract : Two-dimensional nanosheets show promise as electrode materials for high electrochemical performance lithium-ion batteries owing to their unique properties. However, individual nanosheets cannot meet all the required properties for batteries in one material to achieve optimal performance. Here, we demonstrate a new type of two-dimensional heterostructure cathode material for lithium-ion batteries by inkjet printing a composite ink based on high capacity V2 O5 nanosheets and high electronic conductivity Ti3 C2 Tx nanosheets. The excellent electronic conductivity of Ti3 C2 Tx nanosheets and layer-by-layer heterostructure design enable fast electron transport and minimization of detrimental volume changes during the electrochemical process, respectively. The printed cathodes exhibit a high capacity of 321 mAh g −1 at 1C, high-rate capability of 112 mAh g −1 at 10.5C and good cycling stability after 680 cycles with 91.8% capacity retention, indicating high electrochemical performance of the printed heterostructure cathode. This work opens new opportunities of two-dimensional heterostructures for high performance energy storage applications.